Association of tongue brushing with the number of fungiform taste buds and taste perception: A preliminary study using confocal laser scanning microscopy in combination with a filter-paper disc method. (December 2017) - Kobayashi, Junichi; Saito, Takehisa; Ito, Tetsufumi; Yoshimura, Hitoshi; Matsuda, Shinpei; Yoshida, Hisato; Fujita, Ryousuke; Sano, Kazuo
Highlights: Association of tongue brushing with fungiform taste buds and sensation was investigated. Confocal laser scanning microscopy and a filter-paper disc method were used. Excessive tongue brushing may have an association with the decreased number of fungiform papillae and taste buds and decreased taste sensation. Abstract: Objective: The aim of this study was to investigate the association of tongue brushing with the number of fungiform taste buds and taste perception using a confocal laser scanning microscopy in combination with a filter-paper disc method (FPDM). Methods: Twenty-four subjects with or without a habit of tongue brushing (11 males and 13 females, 20–46 years old) participated in this study. Nine of the 24 subjects had no habit of tongue brushing (Group 1, n = 9). Fifteen subjects had a habit of tongue brushing, and the brushing regions of the tongue were as follows: central region (Group 2, n = 7), or entire region (Group 3, n = 8) of the tongue dorsum. Using confocal laser scanning microscopy, the average number of taste buds per fungiform papilla (FP) was counted. Taste perception was evaluated using an FPDM. These observations were performed in the midlateral region of the tongue since the distribution of fungiform papillae is large in the midlateral region compared to that in the central region. Results: The subjects in Group 3 showed a significantly decreased number of fungiform taste buds compared to Group 1 and Group 2. Group 3 also showed significantly higher FPDM scores than the other two groups. Conclusions: Excessive tongue brushing of the entire tongue dorsum, including the midlateral region, may have an association with the decreased number of FP and taste buds and decreased taste sensation. To avoid these conditions, instituting proper tongue brushing methods, such as limiting it to the central region of the tongue and using a light touch, is suggested and is important for the subjects who are eager to participate in tongue brushing.